The influence of subjective loss perception on individual prediction of pension scheme rate of return - Bobrowska, Agnieszka; Maciejasz-Świątkiewicz, Marta (Wpływ subiektywnej oceny straty na szacowanie indywidualnej stopy zwrotu z systemu emerytalnego, 2012)
The article presents how people subjectively measure the effects of the Polish retirement system. To verify this a survey was conducted in which respondents had to estimate the sum that was going to be collected in the retirement account through the institution of social insurance by 10, 20 or 30 years and individually. The sum was going to be collected thanks to regular payments of 5000 PLN every year. The hypotheses put at the beginning were fully confirmed and the survey proved that hyperbolic discounting really works and that the level of subjective rate of loss is quite high
Nauki o Finansach = Financial Sciences, 2012, Nr 1 (10), s. 11-20
Keywords: hyperbolic discounting; pension scheme; retirement savings; system emerytalny; dyskontowanie hiperboliczne; oszczędzanie na emeryturę